Exploring Factors Associated with Academic Motivation and College and Career Readiness of Rural Adolescents - Knox, Peter N. (The Rural educator (Fort Collins, Colo.), 2023)
Yet subsets of previous educational research offer insight into various components that may work in tandem to influence rural adolescent postsecondary outcomes. [...]I situate the current study within three bodies of existing scholarship. [...]I discuss previous research centered around adolescent academic motivation-critical to college and career readiness-and how it is also influenced by the individual and contextual elements noted above. Poverty remains a persistent and pervasive barrier that impacts rural adolescents and schools, with rates of child poverty and deep familial poverty (i.e., family income falls below half the poverty line) nearly 20% higher in rural communities relative to the national average (Schaefer et al., 2016). Nelson (2016) identified overlapping features and attributes of family, school, and community social capital within rural communities that translate into educational attainment for rural adolescents.